SAT0222 Effects of Tofacitinib on MRI Endpoints in Methotrexate-Naive Early Rheumatoid Arthritis: A Phase 2 MRI Study with Semi-Quantitative and Quantitative Endpoints. (9th June 2015) - Conaghan, P.G.; Østergaard, M.; Bowes, M.A.; Wu, C.; Fuerst, T.; van der Heijde, D.; Hrycaj, P.; Xie, Z.; Zhang, R.; Wyman, B.T.; Bradley, J.; Soma, K.; et al.
Abstract : Background: Inflammation of the synovium and in particular the bone marrow, as assessed by magnetic resonance imaging (MRI), have been identified as prognostic indicators of structural joint damage in patients (pts) with rheumatoid arthritis (RA). Tofacitinib is an oral Janus kinase inhibitor for the treatment of RA. Inhibition of structural damage has been shown using conventional radiography in pts receiving tofacitinib for moderate to severe RA. 1, 2 Objectives: To explore the effects of tofacitinib, with or without methotrexate (MTX), on a range of sensitive MRI endpoints. Methods: This was an exploratory, Phase 2, randomised, double-blind, parallel group, multicentre study (A3921068; NCT01164579 ) in MTX-naive adults with early active RA (duration ≤2 years) and evidence of clinical synovitis in an index wrist or metacarpophalangeal (MCP) joint. Pts were randomised 1:1:1 to receive tofacitinib 10 mg twice daily (BID) + MTX, tofacitinib 10 mg BID + placebo (PBO) or MTX + PBO, for 1 year. MRI endpoints in the wrist and MCP joints were assessed using 3 methods: OMERACT RAMRIS; a novel automated method quantifying RAMRIS components using Active Appearance Modelling (RAMRIQ; Imorphics UK); and dynamic quantitative MRI (Dynamika, UK). Evaluable pts were assessed using a mixed effect model for repeated measures to evaluate endpoints (statistical significance at 10% [2-sided] level). Scoring was performed by one centralised reader blinded to time point and treatment. Results: Of 109 pts randomised and treated, most were female and Caucasian. Disease duration was consistent with early RA (mean: 0.6–0.8 years). Mean age, disease activity and MRI evaluations were similar across treatment groups at baseline (BL). More pts from the tofacitinib + MTX and tofacitinib + PBO groups completed the study (n=28, n=27, respectively) vs MTX + PBO (n=21). Mean BME improvements, measured with RAMRIS and RAMRIQ only, were statistically greater in both tofacitinib groups vs MTX + PBO at M3, M6 (primary; RAMRIS) and M12. Synovitis improvements were observed in all groups; numerical improvements were observed in both tofacitinib groups vs MTX + PBO with RAMRIS, but statistically significant differences were observed for both tofacitinib groups across time points with the more sensitive RAMRIQ, which was consistent with dynamic MRI findings (Table 1 ). Significantly less erosive damage was seen using RAMRIS and RAMRIQ in both tofacitinib groups vs MTX + PBO at M6 and M12 (Table 1 ). Conclusions: These results provide consistent evidence using 3 different MRI assessment technologies that tofacitinib treatment leads to early reduction of inflammation and lack of progression of structural damage. References: Lee EB et al. N Engl J Med 2014; 370:2377-86. 2. van der Heijde, et al. Arthritis Rheum 2013; 65:559-70. Acknowledgements: RAMRIS data presented previously (Conaghan P, et al. Arthritis Rheum 2014; 66 (11): S375 abs 849) and reproduced with permission from Arthritis and Rheumatism. All aspects of this study were funded by Pfizer Inc. Editorial support was provided by C Cridland of CMC, and funded by Pfizer Inc. Disclosure of Interest: P. Conaghan Consultant for: AbbVie, Merck, Novartis, Pfizer Inc, Roche, and UCB, Speakers bureau: AbbVie, Merck, Novartis, Pfizer Inc, Roche, and UCB, M. Østergaard Grant/research support from: Abbott/AbbVie, Centocor, Merck, and Schering-Plough, Consultant for: Abbott/AbbVie, Bristol-Myers Squibb, Boehringer-Ingelheim, Eli-Lilly, Centocor, GSK, Janssen, Merck, Mundipharma, Novo, Pfizer Inc, Schering-Plough, Roche, UCB, and Wyeth, M. Bowes Consultant for: Pfizer Inc, C. Wu Consultant for: Pfizer Inc, T. Fuerst Consultant for: Pfizer Inc, D. van der Heijde Consultant for: Pfizer Inc, P. Hrycaj Grant/research support from: Pfizer Inc, Consultant for: Pfizer Inc, Z. Xie Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, R. Zhang Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, B. Wyman Shareholder of: Pfizer Inc, J. Bradley Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, K. Soma Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, B. Wilkinson Shareholder of: Pfizer Inc, Employee of: Pfizer Inc